Enhanced upconversion luminescence of NaYF4:Yb, Er microprisms via La3+ doping. (February 2017) - Fu, Junxiang; Zhang, Xiaozeng; Chao, Zhicong; Li, Zibo; Liao, Jinsheng; Hou, Dejian; Wen, Herui; Lu, Xiaoneng; Xie, Xinrong
Abstract: A series of β-NaYF4 : Yb, Er micro-prisms codoped with La 3+ (0–30 at%) were synthesized via hydrothermal process. Upon 980 nm excitation at room temperature, 20 mol% La 3+ codoped sample shows a maximum upconversion emission intensity. Excitation power density dependencies of UC luminescence and the decay curves were investigated. The UCPL decay is evidently monoexponential for all samples and La 3+ doping did not significantly change the decay time. In this particular case, we found the napierian logarithm of the UC emission intensity (lnI) had a good linear relationship with the cell lattice parameters. This correlation may be helpful for design and fabrication of high performance upconversion materials. Highlights: Micron sized β-NaYF4: Yb, Er prisms and plates were obtained via La 3+ ion doping. The upconversion emission intensity of NaYF4 :Yb, Er arrived the maximum when 20 mol% La was codoped. The relation between the upconversion emission intensity and cell parameters was revealed.